Prenatal alcohol exposure and prenatal stress differentially alter glucocorticoid signaling in the placenta and fetal brain. (7th February 2017) - Lan, N.; Chiu, M.P.Y.; Ellis, L.; Weinberg, J.
Highlights: Both PAE and PS dams had higher corticosterone levels. 11β-HSD2 protein levels were increased in PAE and unchanged in PS placentae. PS female fetuses had higher MR protein levels in the hippocampus and amygdala compared to C female fetuses. PS female fetuses had lower GR protein levels in mPFC compared to C female fetuses. Both PAE and PS attenuated the sexually dimorphic expression of MR, GR and the MR/GR ratio seen in C fetuses. Abstract: Adverse intrauterine environments increase vulnerability to chronic diseases across the lifespan. The hypothalamic–pituitary–adrenal (HPA) axis, which integrates multiple neuronal signals and ultimately controls the response to stressors, may provide a final common pathway linking early adversity and adult diseases. Both prenatal alcohol exposure (PAE) and prenatal stress (PS) induce a hyperresponsive HPA phenotype in adulthood. As glucocorticoids are pivotal for the normal development of many fetal tissues including the brain, we used animal models of PAE and PS to investigate possible mechanisms underlying fetal programing of glucocorticoid signaling in the placenta and fetal brain at gestation day (GD) 21. We found that both PAE and PS dams had higher corticosterone (CORT) levels than control dams. However, 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) enzyme levels were increased in PAE and unchanged in PS placentae, although there were no differences in 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) levels. Moreover, only PAE fetuses showed decreased body weight and increased placental weight, and hence a lower fetal/placental weight ratio, a marker of placenta efficiency, compared to all other prenatal groups. Importantly, PAE and PS differentially altered corticosteroid receptor levels in placentae and brains. In the PS condition, maternal CORT was negatively correlated with both 11β-HSD1 and mineralocorticoid receptor (MR) protein levels in male and female placentae, whereas in the PAE condition, there were trends for a positive correlation between maternal CORT and 11β-HSD1, regardless of sex, and a negative correlation between maternal alcohol intake and MR in male placentae. In fetal brains, sexually dimorphic changes in MR and glucocorticoid receptor (GR) levels, and the MR/GR ratio seen in C fetuses were absent in PAE and PS fetuses. In addition, PS but not PAE female fetuses had higher MR and lower GR expression levels in certain limbic areas compared to C female fetuses. Thus the similar adult HPA hyperresponsive phenotype in PAE and PS animals likely occurs through differential effects on glucocorticoid signaling in the placenta and fetal brain.